Scripta signa vocis. Studies about Scripts, Scriptures, Scribes and Languages in the Near East presented to J. H. Hospers by his pupils, colleagues and friends - Leemhuis, F.; Jongeling, K.; Vanstiphout, H. L. J. (Fs Hospers, 1986)
Paralleltitel in Sumerisch, Hebräisch, Syrisch und Arabisch.